Intersecting motivations for leaving abusive relationships, substance abuse, and transactional sex among HIV high-risk women - Naomi David; Sophia Hussen; Dawn Comeau; Ameeta Kalokhe (Georgia Southern University, 2016)
Background: Women bear a significant burden of the HIV epidemic in the United States. Women classified as 'HIV high-risk' often bring co-existing histories of intimate partner violence (IPV), drug use, and transactional sex. To help inform future comprehensive HIV prevention strategies, we aimed to explore common motivating reasons and barriers to leaving and/or terminating engagement in each of these riskpromoting situations. Methods: Between August and November 2014, in-depth interviews were conducted with 14 HIV highrisk women in Atlanta, Georgia who had experienced IPV in the previous 12 months, and used drugs and/or engaged in transactional sex in the previous five years. Participants were asked about histories of IPV, drug use, and/or engagement in transactional sex, and the motivating reasons and barriers to terminating each. Results: Women reported a range of motivating reasons for leaving IPV, drug use, and transactional sex. Overlapping themes included impact on children, personal physical health/safety, and life dissatisfaction. Financial need was identified as a common barrier to leaving. Conclusions: Future HIV prevention research should further explore the perceived impact of IPV, drug use, and transactional sex on physical health/safety, life dissatisfaction, one's children, and financial need as motivators and barriers to reducing upstream HIV risk.